VARIATION IN THE DEVELOPMENT OF RED CLOVER (TRIFOLIUM PRATENSE L.) - Radic, Vojo; Komljenovic, Ilija; Petkovic, Borislav; Jovovic, Zoran (Journal of Agricultural Sciences (Belgrade), 2025)
The goal of this research was to study the morphological characteristics of red clover in the conditions of the mountainous area of the Banja Luka region. Experimental tests were carried out on eight genotypes of red clover over several years. There were no significant differences between the average values of stem thickness and plant height of the two first cuttings from the two years of testing, the first cutting of the second year had the highest height (80,0 cm). Genotype 1 had the highest average height (78,0 cm) and leaflet length (45.52 mm). Genotype 6 had the lowest average plant height (74,0 cm), number of stems (7,15), stem thickness (3,31 mm) and leaflet length (36,68 mm). The largest number of stems per plant had genotype 3 in the first cutting of the second year (10,40), with this genotype and for this trait the highest variability was obtained (23,44%). Genotypes 6 and 8 had the widest leaflet in the first cut of the second year of testing (28,94 and 28,93 mm) and genotype 4 had the largest average (25,19 mm). Besides of the trait of plant height, no significant differences between genotypes were obtained, statistically significant differences were obtained for all the other tested traits between clover cuts and genotypes. The average values of the number of stems per plant, the length and width of leaflet in the first clever cut of the first, and second clever cut of the second year were not statistically significantly different. Red clover is the most productive in the first cutting of the second year of life, this was also confirmed in these studies, in which the highest values of most of the tested traits were obtained in that cutting.
Keywords: Red clover, cut, genotype, morphological traits, variability.